Firing versus continuing employment if an economic setback is expected - Matthias Göcke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
A simple model evaluating a firm’s optimal employment reaction to an imminent recession is presented. Firing costs shelter employment – and this effect is typically amplified by uncertainty due to an option value of waiting. However, this job protection effect is reduced if the expected probability of a setback increases, and if the expected duration and size of a recession grows. If a severe recession is expected with a high probability the option to wait with firing looses its value, thus, immediate layoffs and market exits become the optimal strategy even before the recession turns out to be actual.
Keywords: D81; J63; 330; Firing costs and uncertainty; probability; duration and size of recession